2014
DOI: 10.2337/diaclin.32.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults' Perceived Challenges With Health Care Providers Treating Their Type 2 Diabetes and Comorbid Conditions

Abstract: IN BRIEF Type 2 diabetes and comorbidity represent serious health problems to the aging population. This qualitative study aimed to describe older adults' perceived challenges with providers treating their type 2 diabetes and other chronic conditions. Older adults perceived a general unwillingness from their providers to treat their multiple health conditions and address their individual preferences for care. Older adults may require more in-depth communication with their providers in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Beverly et al found that people with diabetes felt providers did not understand or appreciate the difficulties of living with diabetes or its' complications and many noted that that their care was not individualized. [3] This may be partially related to lack of knowledge about diabetes care among health care practitioners. [4] Griffis et al discovered that acute care nurses had large gaps in their knowledge of diabetes specifically in the areas of therapies and medications.…”
Section: Introductionmentioning
confidence: 99%
“…Beverly et al found that people with diabetes felt providers did not understand or appreciate the difficulties of living with diabetes or its' complications and many noted that that their care was not individualized. [3] This may be partially related to lack of knowledge about diabetes care among health care practitioners. [4] Griffis et al discovered that acute care nurses had large gaps in their knowledge of diabetes specifically in the areas of therapies and medications.…”
Section: Introductionmentioning
confidence: 99%
“…25,28,30,37,39,42,43,45,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] These comprised 79 research papers and 10 guidelines or discussion pieces. Other papers cited in this chapter are for background information and did not undergo full data extraction.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…A key element of achieving a person-centred or partnership approach to care is building a long-term trusting relationship with the people living with dementia and diabetes and their family 69,70,72,73,79,102,125,142 that involves listening and valuing the patient's subjective health experiences:…”
Section: Trusting Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations